Síntese, caracterização e estudo do comportamento térmico de alguns compostos organometálicos de estanho e metais de transição - Jonas Leal Neto (2006)
This work describes results of synthesis and characterisation of organotin oxides and heterometallic complexes containing tiniron and tinmolybdenum bonds. Afterwards, it has been studied the thermal behaviour of all compounds and their use as precursors for oxides in pyrolysis experiments. Chapter 2 describes pyrolysis experiments in N2, air and O2 atmosphere for Sn3O3Bu6 (I) e Sn4O6Bu4 (II). Results obtained for all decomposition products indicated the formation of nanometric SnO2 powder as the main constituent in an oxidizing atmosphere. Chapter 3 and 4 comprises the synthesis and characterisation of tin-transition metals compounds. Complexes [Fe(5-C5H5)(CO)2]2SnCl2 (1), [Fe(5-C5H5)(CO)2]SnCl3 (2), [Mo(5-C5H5)(CO)3]2SnCl2 (3) e [Mo(5-C5H5)(CO)3]SnCl3 (4), although described in literature, were important in the pyrolysis experiments to obtain tin-transition metal oxides. Reactions involving compound 2 and ligands derived from 2,6-pyridinedicarboxylic acid (H2PDC) and 2-mercaptopyridine (2-PySH) yielded two new heterometallics complexes: [Fe(5-C5H5)(CO)2]2Sn(PDC) (5) e [Fe(5-C5H5)(CO)2]2Sn(2-PyS)2 (6). The structures of compounds 4 e 5 were determined by X-rays crystallography. In complex 5, PDC anion behaves as a tridentate ligand coordinated by one oxygen atom (from each carboxylate group) and by pyridinic nitrogen, showing a one-to-one proportion. For compound 6, two 2-PyS anions behaved as a monodentate ligand coordinated, by thiolate sulfur in substitution to the chlorides. Chapter 5 presents the pyrolysis experiments for all heterometallic compounds (except for complex 6) starting from 100 until 900 oC. The TG/DTG, XRD and 57Fe and 119Sn Mössbauer spectroscopy results showed formation of Sn(IV), Fe(III) and Mo(VI) oxides. Pyrolysis experiments of compounds 1, 2 and 5 have shown a mixture of SnO2 and -Fe2O3. For compounds 3 and 4 only SnO2 was obtained once the sublimation of MoO3 was detected since it has condensed at the end of the quartz tube. The sample morphology investigated by SEM revealed the sinterization of some of the oxides. It also indicated the formation of SnO2 grains having diameters within 150 and 800 nm.